ASUU Strike and Nigerian Educational System: An Empirical Investigation of the Nigerian Tertiary Institution - O., Monogbe, B.; G., Monogbe, T. (American Journal of Social Sciences and Humanities, 2019)
Education is the panacea that liberates an individual from slavery while the university is the brain box of a nation. As such, this study set out to examine the extent to which academic staff union of the university (ASUU) strikes influences tertiary educational system in Nigeria. The study adopts the descriptive research design where questionnaires were distributed to 600 students of the four target universities in Rivers and Ekiti state. Student performance, quality of education and permanent solution to education problems were measures of the Nigerian educational system while ASUU strike remains the dimension. Findings from the study reveal that quality of education and student performance is negatively influenced by incessant ASUU strike such that increase in ASUU strike is capable of decreasing student performance in the Nigerian universities. The study thus concludes that incessant strike actions culminate into the erosion of academic quality, robbing off academic time from school administrators and upon resuming from a strike, academic work is bound to the rushed. As such, this study recommends that universities monitoring committee should be formulated whose responsibility will be to liaise with the union on the recent challenges the universities are facing and relate back to the government for quick action. This will further help in reducing the incessant industrial action of ASUU and thus boost the education system in Nigeria.